Does Improving Geographic Access to VA Primary Care Services Impact Patients' Patterns of Utilization and Costs? - John C. Fortney; Matthew L. Maciejewski; James J. Warren; James F. Burgess (SAGE Publishing, 2005)
The Department of Veterans Affairs (VA) has been establishing community-based outpatient clinics (CBOCs) across the country to improve veterans' access to and use of primary care services, thereby decreasing the need for costly specialty outpatient and inpatient care. Using a quasi-experimental, pre-post study design, we examined whether the establishment of CBOCs has affected access, use, and costs for VA patients residing in their catchment areas. Most patients residing in CBOC catchment areas did not receive care at CBOCs, resulting in only small increases in primary care utilization. While CBOCs improved veterans' access, they had little impact on overall patterns of utilization and cost.